Primary pelvic hydatid cyst presenting with obstructive uropathy and renal failure. - Seenu, V. (BMJ Group, 1994)
Primary pelvic hydatid cyst is a rare entity. Pelvic hydatid cysts usually present with pressure symptoms involving adjacent organs (bladder and rectum usually). A case of primary pelvic hydatid cyst presenting with obstructive uropathy leading to chronic renal failure is presented. A combination of preoperative albendazole therapy of 1.2 g/day for 8-12 weeks and surgical excision were effective in alleviating the symptoms and improving the renal function.